Premature placental aging in term small‐for‐gestational‐age and growth‐restricted fetuses. (12th April 2019) - Paules, C.; Dantas, A. P.; Miranda, J.; Crovetto, F.; Eixarch, E.; Rodriguez‐Sureda, V.; Dominguez, C.; Casu, G.; Rovira, C.; Nadal, A.; Crispi, F.; Gratacós, E.
ABSTRACT: Objective: To perform a comprehensive assessment of the placental aging process in small term fetuses classified as being small‐for‐gestational age (SGA) or having fetal growth restriction (FGR) through analysis of senescence and apoptosis markers. Methods: This was a prospective nested case–control study of singleton pregnancies delivered at term, including 21 control pregnancies with normally grown fetuses and 36 with a small fetus classified as SGA (birth weight between the 3 rd and 9 th percentiles and normal fetoplacental Doppler; n  = 18) or FGR (birth weight < 3 rd percentile and/or abnormal cerebroplacental ratio and/or uterine artery Doppler; n  = 18). Telomerase activity, telomere length (quantified by comparing the amount of amplification product for the telomere sequence (T) to that of a single copy of the gene 36B4 (S)) and RNA expression of senescence (Sirtuins 1, 3 and 6) and apoptosis (p53, p21, BAX and Caspases 3 and 9) markers (analyzed using the 2 –ΔΔCt method) were determined in placental samples collected at birth and compared between the three groups. Results: Compared to pregnancies with a normally grown fetus, both SGA and FGR pregnancies presented signs of accelerated placental aging, including lower telomerase activity (mean ± SD, 12.8 ± 6.6% in controls vs 7.98 ± 4.2% in SGA vs 7.79 ± 4.6% in FGR; P  = 0.008), shorter telomeres (mean ± SD T/S ratio, 1.20 ± 0.6 in controls vs 1.08 ± 0.9 in SGA vs 0.66 ± 0.5 in FGR; P  = 0.047) and reduced Sirtuin‐1 RNA expression (mean ± SD 2 –ΔΔCt, 1.55 ± 0.8 in controls vs 0.91 ± 0.8 in SGA vs 0.63 ± 0.5 in FGR; P  = 0.001) together with increased p53 RNA expression (median (interquartile range) 2 –ΔΔCt, 1.07 (0.3–3.3) in controls vs 5.39 (0.6–15) in SGA vs 3.75 (0.9–7.8) in FGR; P  = 0.040). FGR cases presented signs of apoptosis, with increased Caspase‐3 RNA levels (median (interquartile range) 2 –ΔΔCt, 0.94 (0.7–1.7) in controls vs 3.98 (0.9–31) in FGR; P  = 0.031) and Caspase‐9 RNA levels (median (interquartile range) 2 –ΔΔCt, 1.21 (0.6–4.0) in controls vs 3.87 (1.5–9.0) in FGR; P  = 0.037) compared with controls. In addition, Sirtuin‐1 RNA expression, telomerase activity, telomere length and Caspase‐3 activity showed significant linear trends across groups as severity of the condition increased. Conclusions: Accelerated placental aging was observed in both clinical forms of late‐onset fetal smallness (SGA and FGR), supporting a common pathophysiology and challenging the concept of SGA fetuses being constitutionally small. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations. This article has been selected for Journal Club. Clickhere to view slides and discussion points.